الــلغة التأويلية في شعر ابن الخلوف القسنطيني " ( التائية الكبرى أنموذجا) - معـاش, حيـاة (Sciences humaines, 2014)
سأحاول من خلال هذا المقال البحث عن المصادر المكونة لنص القصيدة جماليا و فكريا سواء عن طريق البحث عن اللغة العليا أو اللغة الثانية؛ لأنها تعد ملحمة لما فيها من سرد تاريخي، و ما تحمله من صراع النفس و العواطف بين الخير و الشر، ومعان روحية سامية من خلال أفكاره الصوفية.   I will try in this article to research for many resources wich contains of the poem in beautiful and thinking way,either from the researching way, superior language or in the second one. Because it becomes the meathouse in the historicallytelling and the containing of the good and the bad things in the emotions of the humanity during the mysticism thinking.